Aplikasi Teori Dominasi Jarak Satu Pada Penempatan SPBU Di Kabupaten Jember - Mahmudah, Muhlisatul (Kadikma, 2022)
Many Public Gas Stations (SPBU) in Jember Regency has an impact on the inefficiency of Jember Regency area which should be used for other developments which also benefit the community. Therefore, this research useful to investigate the dominating number of one distance in the shackle operation graph that is shackle (), and the placement of SPBU in Jember Regency so that its placement can reach all areas of Jember Regency. This research uses axiomatic deductive method and pattern detection, which determine the dominating sets in a way that the minimum cardinality is found and produces new theorems that have been deductively proven so the truth is generally valid.